Patterns of accidental craniocerebral injury occurring in early childhood. Issue 10 (6th August 2013) - Thomas, A G; Hegde, S V; Dineen, R A; Jaspan, T
Abstract : Objective: To describe the range of intracranial injuries encountered in 0–2-year-olds in cases of accidental head injury where the mechanism of trauma was well characterised and to assess the clinical consequences. Design: A retrospective review of imaging and clinical data. Setting: Two tertiary paediatric referral centres. Patients: All children aged 0–2 undergoing cranial CT as indicated by National Institute for Health and Clinical Excellence guidance for head injury from 2006 to 2011. After exclusion criteria, 149 patients were included. Main outcome measures: Rates of skull fracture, intracranial haemorrhage, parenchymal injuries and ischaemic change per type of mechanism of injury. Rates of neurological sequelae on follow-up. Results: Skull fractures were demonstrated in 54 (36%) patients of whom 17 (11%) had thin underlying subdural haemorrhage (SDH). Extradural haemorrhage complicated one fracture and two cases of isolated subdural haematomas were seen without skull fracture. Radiologically evident brain parenchymal injuries were present in three patients, all with mechanisms of injury involving high levels of force; severe neurological sequelae were only seen in one patient, who had diffuse hypoxic–ischaemic damage at presentation and whose (accidental) mechanism of injury involved extensive acceleration/deceleration/translational forces. Conclusions: Skull fractures and focal SDH are relatively common following minor trauma in this age group but in the vast majority of cases there are no long-term neurological sequelae. Conversely, diffuse brain injury with severe subsequent neurological impairment was only seen in patients with a correspondingly severe mechanism of injury.